A review on computational dynamic analysis of composite beam structures - Irandoust , Kiarash (Journal of Composites and Compounds, 2025)
This review has thoroughly examined recent developments in the dynamic behavior of composite beam structures. The results indicate that advanced techniques like finite element analysis (FEM), chiral uniform formulation (CUF), and time history analysis have made it possible to accurately model dynamic properties, including vibration, stability, and damping of beam structures. On the downside, there is still a great need for the development of numerical models that are more efficient at modeling present nonlinear effects, separating layers, and interacting with the ambient structure. Future developments in the design of multiscale algorithms and the incorporation of machine learning technologies will help lead to faster and more accurate ways to analyze the dynamic responses of beam structures.